The Effectiveness Of An Internship Program: A Case Study At PT Kulina Putra Madya - Faruq, Daffa Al; Linando, Jaya Addin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study examines the effectiveness of the Certified Internship and Independent Study Program (MSIB) through a qualitative case study of interns placed at PT Kulina Putra Madya (KPM) under APINDO coordination. Despite the program’s promise of strategic roles as "business consultants" for MSMEs, interns faced a significant expectation-reality gap, often assigned administrative or operational tasks with minimal mentorship. Interviews with three interns revealed three key issues: (1) misalignment between job descriptions and actual responsibilities, (2) structural challenges such as poor communication and lack of guidance, and (3) self-initiated adaptation strategies like peer learning and resilience-building. Findings indicate that while interns developed soft skills (e.g., adaptability), the program failed to deliver promised professional development. The study underscores the need for clearer job design, structured mentoring, and stronger institutional coordination to align internships with educational objectives. Recommendations include formalized learning agreements, host company training, and integrating student-led adaptive practices into program design. These improvements could enhance both intern satisfaction and the program’s credibility in bridging academia and industry.